Marker-assisted selection and use of molecular markers in sunflower breeding for resistance to diseases and parasites - Kucherenko, Ye.; Zviahintseva, A.; Kobyzeva, L.; Kolomatska, V.; Makliak, K.; Vasko, N.; Zuieva, K.; Lutsenko, T. (The Journal of V.N.Karazin Kharkiv National University. Series «Biology», 2022)
Recently, the problem of phytosanitary condition of sunflower crops has been exacerbated, which is associated with violation of crop rotations and, as a consequence, spread of common diseases. Selection for resistance to biotic factors requires comprehensive research into the crop biology and pathogens. The use of starting material, which is resistant to major pathogens and environmental stressors, in selection is a prerequisite for the breeding of highly productive hybrids. Significant progress in the breeding of heterosis sunflower hybrids has been achieved primarily due to stable inbred lines. However, their creation is time-consuming, taking 8-12 years. Selection of desirable genotypes and initial forms for crossing is complicated by the fact that it is driven by a set of polygenic traits that are prone to significant modification variability. The use of molecular genetic markers is a way to accelerate breeding. Marker-assisted selection breeding (MAS) has been theoretically justified in numerous publications and implemented in most breeding institutions around the world. However, in domestic breeding programs, MAS has not become widespread compared to traditional methods. Nevertheless, this breeding trend opens new opportunities for studying genetic diversity and determining kinship at the intraspecies and genus levels. The review provides information on the status and prospects of implementation of MAS in traditional plant breeding and highlights the achievements of modern biotechnology in sunflower breeding for resistance to biotic factors owing to molecular genetic markers. The MAS principles are outlined and the advantages of this method are described. Specific examples of application of the molecular approach during the development of starting material of sunflower for breeding for resistance to common diseases and parasites are given. The main stages and components of PCR analysis are also described. Inbred sunflower lines – carriers of the gene for resistance to the downy mildew pathogen are characterized and genetic passports using STS markers to the Pl6 locus have been formalized for 13 sunflower lines.